Metabolic syndrome and pesticides: A systematic review and meta-analysis. (15th July 2022) - Lamat, Hugo; Sauvant-Rochat, Marie-Pierre; Tauveron, Igor; Bagheri, Reza; Ugbolue, Ukadike C.; Maqdasi, Salwan; Navel, Valentin; Dutheil, Frédéric
Abstract: The relation between pesticides exposure and metabolic syndrome (MetS) has not been clearly identified. Performing a systematic review and meta-analysis, PubMed, Cochrane Library, Embase, and ScienceDirect were searched for studies reporting the risk of MetS following pesticides exposure and their contaminants. We included 12 studies for a total of 6789 participants, in which 1981 (29.1%) had a MetS. Overall exposure to pesticides and their contaminants increased the risk of MetS by 30% (95CI 22%–37%). Overall organochlorine increased the risk of MetS by 23% (14–32%), as well as for most types of organochlorines: hexachlorocyclohexane increased the risk by 53% (28–78%), hexachlorobenzene by 40% (0.01–80%), dichlorodiphenyldichloroethylene by 22% (9–34%), dichlorodiphenyltrichloroethane by 28% (5–50%), oxychlordane by 24% (1–47%), and transnonchlor by 35% (19–52%). Sensitivity analyses confirmed that overall exposure to pesticides and their contaminants increased the risk by 46% (35–56%) using crude data or by 19% (10–29%) using fully-adjusted model. The risk for overall pesticides and types of pesticides was also significant with crude data but only for hexachlorocyclohexane (36% risk increase, 17–55%) and transnonchlor (25% risk increase, 3–48%) with fully-adjusted models. Metaregressions demonstrated that hexachlorocyclohexane increased the risk of MetS in comparison to most other pesticides. The risk increased for more recent periods (Coefficient = 0.28, 95CI 0.20 to 0.37, by year). We demonstrated an inverse relationship with body mass index and male gender. In conclusion, pesticides exposure is a major risk factor for MetS. Besides organochlorine exposure, data are lacking for other types of pesticides. The risk increased with time, reflecting a probable increase of the use of pesticides worldwide. The inverse relationship with body mass index may signify a stockage of pesticides and contaminants in fat tissue. Graphical abstract: Image 1 Highlights: The relation between pesticides exposure and metabolic syndrome (MetS) was unclear. We conducted meta-analysis on the risk of MetS following pesticides exposures. Overall exposure to pesticides and their contaminants increased the risk of MetS by 30%. Hexachlorocyclohexane increased the risk of MetS in comparison to most other pesticides. In conclusion, we showed that pesticides exposure is a major risk factor for MetS.